Dual-Amplifying Electrochemiluminescence Sensor Based on CdS QDs@HKUST-1/MWCNTs Composite for Sensitive Catechol Assay. Issue 12 (1st December 2022) - Zhao, Wenrui; Wang, Beibei; Ji, Xueping; Kang, Kai; Wang, Bing; Wang, Lin; Ren, Jujie
Abstract : Herein, a novel electrochemiluminescence (ECL) sensor was developed using a dual signal amplification mechanism based on a typical HKUST-1 metal-organic framework, [Cu3 (BTC)2 (H2 O)3, BTC=1, 3, 5-benzene tricarboxylate], CdS quantum dots (QDs) and multi-walled carbon nanotubes (MWCNTs) for ultrasensitive determination of catechol. HKUST-1 not only has a dispersion effect to carry more CdS QDs for enhancing stability, but also acts as effective catalyzer to accelerate the transformation of persulfate ion (S2 O8 2− ) for generating more sulfate radical anions (SO4 − ), therefore amplifying the signal of the ECL sensor. Meanwhile, the introduction of MWCNTs to the ECL process could promote the electron transfer rate and accelerate the kinetics of the electro-catalytic reaction attributing to its stronger conductivity, achieving dual-amplifying effect, which could obviously increase the sensitivity of the ECL sensor. The proposed sensor displayed a wide linear range of 1 × 10 −7 − 1 × 10 −3 M and a low detection limit of 3.8 × 10 −8 M with excellent stability, high repeatability and outstanding anti-interference ability under the optimal conditions. Impressively, the sensor possessed commendable feedback when detecting catechol in real samples. Therefore, this research provided a new strategy combining the advantages of MOFs, QDs and MWCNTs materials for phenolic pollutants detection.